Integrated CRISPR-Cas12a and RAA one-pot visual strategy for the rapid identification of Streptococcus equi subspecies equi - Zu, Haoyu; Sun, Rongkuan; Li, Jiaxin; Guo, Xing; Wang, Min; Guo, Wei; Wang, Xiaojun (Frontiers in Cellular and Infection Microbiology, 2025)
Strangles, a highly contagious disease caused by Streptococcus equi subspecies equi (S.equi), significantly impacts horse populations worldwide, with Iceland as the only exception. This disease poses serious threats to equine health and results in considerable economic losses. Consequently, the accurate, sensitive, and rapid detection of S.equi from clinical samples is essential for early warning and effective disease management. This study introduces a novel detection method that integrates recombinase-aided amplification (RAA) with CRISPR/Cas12a technologies. We specifically designed RAA primers and CRISPR RNA to target the eqbE gene of S.equi, and we have carefully optimized the reaction systems for this purpose. The newly established visual diagnostic method has shown to be highly effective, demonstrating 97.14% specificity and 100% sensitivity, with the capability to detect as few as 5.6×100 copies of the target. This is the first study to propose the combined application of RAA and CRISPR/Cas12a for the on-site rapid detection of S.equi. This is the first study to propose the combined application of RAA and CRISPR/Cas12a for the on-site rapid detection of S.equi, which enables visual point-of-care diagnosis of Strangles.